The Effect of C-Reactive Protein Levels, Neutrophil, and Lymphocyte Count to Mortality of COVID-19 Patients with Sepsis in Referral Hospital - Malikhah, Avina Norma; Dhani Redhono Harioputro; Agung Susanto; Evi Nurhayatun (Indonesian Journal of Tropical and Infectious Disease, 2024)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by infection of Severe Acute RespiratoryDistress Syndrom Coronavirus-2 (SARS CoV-2). COVID-19 patients may develop sepsis, the disregulation ofthe immune system that causes organ dysfunction and life-threatening situations. High mortality of COVID-19and sepsis make it important to study. The purpose of this study is to analyze the effect of CRP levels, neutrophil,and lymphocyte count to mortality of COVID-19 patients with sepsis. This study is an analytic observational studywith a cross-sectional approach. Samples were randomly retrieved of COVID-19 patients with sepsis admittedin referral hospital. Univariate, bivariate, and multivariate analysis used SPSS 26th version of Windows. Theresults of this study indicate a significant effect of CRP levels and neutrophil count on mortality of COVID-19patients with sepsis. Meanwhile, lymphocyte count had no significant effects. The multivariate analysis showedits significance value. Partially, the effect of neutrophils on the patient's mortality has a significant value. Theconclusion of this study is CRP levels and neutrophil count simultaneously have an effect on higher mortality ofCOVID-19 patients with sepsis.